THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROCESS OF TEACHING RUSSIAN IN HIGHER EDUCATION INSTITUTIONS: ASSESSMENT OF EFFECTIVENESS AND IMPACT (American Journal of Interdisciplinary Research and Development, 2025)
The article examines the impact of information and communication technologies (ICT) on the teaching of the Russian language in universities. Special attention is paid to the analysis of the impact of multimedia and Internet resources on improving the quality of education and increasing student motivation. The impact of ICT on the development of key language skills such as listening comprehension, writing, speaking and reading is discussed. The article also presents the results of a study based on surveys of students and teachers, as well as an analysis of educational centers that actively use ICT in teaching. The study showed that ICT significantly increases the effectiveness of learning, enhances student engagement and develops their ability to learn independently.